Enhancing Arabic Speaking Skills: A Study on Instructional Design, Implementation, and Assessment - Sarbaini, Albarra; Rahmi, Novita (Arabiyatuna: Jurnal Bahasa Arab, 2024)
Effective teaching and learning of speaking skills are vital for achieving proficiency in any language, particularly in Arabic, where precise verbal communication is essential. This study investigates the design, implementation, and evaluation of Arabic speaking skills instruction at Institut Agama Islam Negeri Metro, aiming to identify best practices and areas for improvement. The research addresses three key questions: how lecturers prepare and comprehend their teaching plans, the effectiveness of various learning designs and strategies, and the challenges students encounter in mastering speaking skills. A qualitative approach was employed, involving interviews with lecturers and observations of speaking classes. The data analysis technique was a qualitative data analysis technique from Miles and Huberman include condensation, display, and verification for conclusion. Findings indicate significant variability in lecturer preparation, with some relying heavily on curriculum materials and others primarily on the syllabus, leading to discrepancies in instructional quality. The design of learning plans also varies, with proactive and reactive approaches affecting the coherence of the teaching process. In implementation, inconsistencies were found in the use of multimedia resources and the emphasis on practical speaking activities, resulting in gaps in student engagement and practice opportunities. Challenges faced by students, particularly in vocabulary and fluency, highlight the need for a more integrative teaching approach that combines grammar, vocabulary, and real-life communication tasks. The study concludes that improving Arabic speaking skills instruction at Institut Agama Islam Negeri Metro requires enhanced lecturer preparation, diverse teaching methods, and more effective assessment strategies. Addressing these issues could significantly improve instructional quality and student outcomes in Arabic language proficiency.